Deferred Tax Asset And Deferred Tax Liability : Studi Eksistensinya Ditinjau Dari Sudut Teori Akuntansi - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2010)
Book income is got from financial statement which is made based on financial accounting standard and taxable income is got from financial statement which is made based on income tax act. Because there are fundamental dffirences used for calculating and arranging, so book income will be different from taxable income. One of the elements which cause these differences is time differences or temporary differences. This time differences can or can't be recorded and presented in a financial statement as deferred tax (interperiod tax allocation or no interperiod tax allocation). There are three methods which can be used to record and report deferred tax: deferred method, asset/liability method and net-of-tax method. Besides to cover time defferences, deferred tax can also be used to record net operating loss (NOL). Each method will use separate account to record deferred tax. From three methods interperiod tax allocation, only asset/liability method which fulfills the presented deferred tax criteria to asset and liability definitions. Deferred tax asset and deferred tax liability which rise from interperiod tax allocation asset/liability method conceptually fulfills asset and liability criteria, so that its existence in balance sheet is strong. Meanwhile, deferred tax asset which comes from NOL carryback and NOL carryforward don't fulfill the asset criteria.